Tune Into Gen-Z Groove: Exploring Gen-Z Reception of Music on Radio Prambors Medan - Miranti, Safira Putri; Sikumbang, Ahmad Tamrin (Lafadz Jaya Publisher, 2024)
This article aims to explore and understand how Generation Z in Medan responds to and interacts with music broadcasted by Radio Prambors, a popular radio station among young people. This study is crucial for identifying the dynamics between the musical preferences of the younger generation and the way radio content is presented in the digital era, as well as its implications for broadcasting strategies. Using a qualitative approach, this research involves in-depth interviews, observations, and document analysis to gather data from Generation Z listeners. Content analysis is used to interpret audience reactions to the music programming, with a source triangulation approach to enhance data validity, combining interviews, social media content analysis, and listener surveys. The research findings reveal three categories of audience reception: hegemony, where listeners fully accept the music choices presented; negotiation, where listeners are satisfied but offer suggestions for a more diverse genre presentation; and opposition, where some less featured music genres cause dissatisfaction among listeners. Furthermore, the interaction between listeners and the radio station shows that Radio Prambors Medan functions not only as a music provider but also as a mediator in a broader communication network that influences the musical tastes and preferences of its listeners. The discussion in this study integrates Manuel Castells' Network Society theory to explain how social and digital networks affect media consumption and interaction among Generation Z, highlighting the crucial role of digital technology adaptation in radio programming strategies. By understanding these dynamics, Radio Prambors Medan can more effectively craft strategies that appeal to its listeners, ultimately maintaining its relevance in the rapidly changing media landscape. The recommendations resulting from this study emphasize the importance of broader digital technology use and more intensive social media interaction to enhance listener engagement and enrich their listening experience.